Impact of Various Transportation Modes on the Air Quality of Dhaka City: A Case Study at Motijheel - Tabassum, Nafisa; Rahman Khan, A F S Ahad; Arefin, Aohona (Journal of Engineering Science, 2023)
Transportation sector significantly contributes to air pollution. This study calculates the daily load of emission of some criteria pollutants (Nitrogen Oxides, Sulfur Oxides, Carbon Monoxide and Suspended Particulate Matter) and hydrocarbons from vehicular fleet at Toyenbee Circular Road, Motijheel, Dhaka. It also analyzes relative contribution of certain types of vehicles to emission of a specific type of pollutant. Primary volume data is collected from field video graphic survey and expansion factors and emission factors are taken from literature. Results show that different types of vehicles contribute to air pollution differently. For Carbon Monoxide and hydrocarbons pollution, motor cars are mainly responsible while bus is the main contributor of Nitrogen Oxides and Sulfur Oxides pollution. Motorcycle is the main contributor of Suspended Particulate Matter pollution in this case. These comparisons imply that it is necessary to determine the focus point of pollution reduction before taking any preventive measures. Journal of Engineering Science 13(2), 2022, 83-89